Determinan Tingkat Pengangguran Dan Kemiskinan Provinsi-Provinsi Di Indonesia - Apristha, Komang Rendy Riyan; Sudibia, I Ketut (Innovative: Journal Of Social Science Research, 2024)
Throughout the first semester of 2021, BKPM has completed 58 percent of stalled investments worth IDR 410 trillion out of a total of IDR 708 trillion. The stalled investment came from 11 companies that had been experiencing obstacles in realizing their investments. The decline in economic movements in Indonesia has led to increasing unemployment. The main objective of this study is to analyze the direct influence of economic growth, HDI, and investment variables on unemployment and poverty and to analyze the indirect influence of economic growth, HDI, and investment variables on poverty through unemployment rate. The design in this study used an associative quantitative research design. The results showed that economic growth, HDI, and investment significantly affect the unemployment and poverty rates of provinces in Indonesia. Specifically, economic growth and HDI have a direct impact on unemployment and poverty, while investment contributes directly to a decrease in unemployment. The results of this study have important implications for economic development policies at the provincial level. They highlighted the need to formulate policies that strengthen economic growth, improve human quality through HDI, and encourage sustainable investment to address the challenges of unemployment and poverty in Indonesia.